ANALYSIS ON THE PREFERENCE OF CUSTOMER IN SHARIA GOLD MORTGAGE LOAN (A Study on PT. Bank Syariah Mandiri Branch of Gresik and PT. Pegadaian (Persero) Branch of Pegadaian Syariah in Kebomas Gresik) - Widyan Apriliska Fajri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
The development of mortgage industry began along with the increasing need of people for money and fund. Mortgage companies in Indonesia are pioneered by PT. Pegadaian (Persero), which shows positive development in every year. Considering the increasing opportunity in mortgage business, sharia banks, Bank Syariah Mandiri for example, have started to turn its head to sharia mortgage business through sharia gold mortgage loan. Then, PT. Pegadaian (Persero) opened its branch of Pegadaian Syariah. Many sharia financial institutions have sharia mortgage product nowadays. It makes people have to choose. This is called as consumer behavior, which later on will create preference. The objective of this study is to identify factors that affect the preference of customer in sharia gold mortgage loan.The result of this study shows that factors affecting the preference of sharia gold mortgage loan customers are place and trust. Most customers choose financial institution located in strategic places, such as the downtown, for easy access. The good reputation of the company will create trust of customers on the sharia financial institution. Those are the considerations of customers in choosing sharia financial institution as their alternate source of funding.Keywords: Sharia financial institution, sharia gold mortgage, consumer behavior, preference